Factors associated with patency following drug-coated balloon angioplasty of hemodialysis access - Guijun Huo; Jianhui Xue; Jin Zheng; Yao Tang; Dayong Zhou (Scientific Reports)
Abstract The purpose of this study was to determine predictors of hemodialysis access patency after drug-coated balloon angioplasty (DCBA) in patients with arteriovenous fistula (AVF). The clinical and imaging data of patients with hemodialysis access dysfunction treated with drug-coated balloon (DCB) in our hospital from January 2020 to January 2024 were analyzed retrospectively, the patency of hemodialysis access was followed up. The length of the DCB is 4 cm. Kaplan-Meier analysis was performed for determination of primary patency and secondary patency in this population. Univariate and multivariate Cox proportional hazards regression analyses were performed to identify predictors of primary patency after DCBA. A total of 173 hemodialysis patients treated with DCB were included in the study. The median survival time of primary and secondary patency were 443 and 1035 days, and the primary patency rates at 6, 12, 18, 24, 30 and 36 months were 85.9%, 64.1%, 34.1%, 21.3%, 12.0% and 6.0%, respectively. The secondary patency rates at 6, 12, 18, 24, 30 and 36 months were 98.8%, 93.8%, 89.8%, 81.9%, 76.1% and 48.6%, respectively. Multivariate analysis using Cox proportional hazard regression models showed that lesion length>4 cm(p=0.002), tandem stenosis(p=0.007) and thrombosis (p < 0.001) were independent risk factors for primary patency after DCBA in patients with AVF. However, lesion length (p=0.021), residual stenosis (p=0.022), and thrombosis (p=0.018) were the independent predictors of primary patency in patients with single lesions.Lesion length>4 cm, tandem stenosis and thrombosis were found to be predictors of primary patency after using 4 cm length DCB. However, in patients with single lesions, lesion length, residual stenosis, and thrombosis serve as independent predictors of primary patency.